Dolores Huerta, winner of the 2010 Steinbeck Award (San Jose, California, 2023)
Dolores Huerta, winner of the 2010 Steinbeck Award. Co-founder of the United Farm Workers Association, Dolores Clara Fernandez Huerta is one of the most influential labor activists of the 20th century and a leader of the Chicano civil rights movement.